Managing complexity and uncertainty in agricultural innovation through adaptive project design and implementation - Bentley, J.W.; Naziri, D.; Prain, Gordon; Kikulwe, Enoch Mutebi; Mayanja, S.; Devaux, A.; Thiele, Graham (Informa UK Limited, 2021)
The recent shift towards agricultural innovation systems recognises that agricultural development is complex and must involve multiple actors. This makes innovation through a project framework inherently challenging. This article draws lessons from a project that fostered post-harvest innovations in Uganda. First, a two-stage design allowed scoping out business cases with partners to identify potential innovations. Second, stakeholders used the Participatory Market Chain Approach (PMCA) to flexibly develop the innovations. Third, flexible funding made it possible to seize new opportunities along the way. Fourth, the project was attentive to surprises in implementation and encouraged reflection.